SENARAI KOSAKATA BAHASA PAPUA DALAM KAMUS BESAR BAHASA INDONESIA PUSAT BAHASA EDISI IV - Neni Sihombing (Multilingual, 2015)
Papua has 307 languages. But, the researchers never investigate about Papuanvocabulary in the Great Dictionary of the Indonesian Language (KBBI) IV edition. This research discusses about (1) Papuan vocabulary in KBBI and (2) itscharacteristics by the form, class, meaning, the possibility of becoming Indonesian vocabulary, inconsistencies, and obstacles. The goals of this research is to describe about (1) Papuan vocabulary in KBBI and (2) its characteristics by the form, class, meaning, the possibility of becoming Indonesian vocabulary, inconsistencies, and obstacles. Method of this research is descriptive analitics. Data was collected by documentation technique. The result of this research is to find 134 Papuan elements entering KBBI and they have form, class, and meaning variously. They are consists of noun, verb, and adjective. Papuan vocabulary has possiblity to enter in KBBI next edition if they don’t have culture concept (specially). However, the writer found inconsistencies and obstacles in the KBBI IV edition.